Laboratory marker profile of patients with Juvenile Idiopathic Arthritis in a paediatric rheumatology outpatient clinic service at Tygerberg Hospital - Wood-Pottle, Leigh-Ann (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMed)--Stellenbosch, 2020.